The role of inflammatory markers in atrial fibrillation: a review - S. V. Grigoryan; K. G. Adamyan; L. G. Azarapetyan (Кардиоваскулярная терапия и профилактика)
This review is focused on the role of latent inflammation in atrial fibrillation (AF) pathogenesis. The modern views and available evidence on the association between the levels of inflammatory markers and AF development and recurrence are presented. The justification for the use of pleiotropic effects of pharmacological therapy in AF prevention and treatment is discussed.